Examining the level of satisfaction with the test components on the desirability of green space (Case study: Emam Reza and Bisetoon hospitals in Kermanshah) - Sahar Toofan; Behnam Shiroyeh Zad (آلودگی‌های محیطی و توسعه پایدار شهری)
The design of treatment spaces is very important, spending long periods of time in treatment environments is usually an unpleasant and very stressful experience for staff, visitors, companions of the patient and the patient. In the present study, the level of satisfaction of the patients of two medical centers, Imam Reza and Bisetoon, Kermanshah, was investigated regarding the factors affecting the desirability of green space. This research is descriptive-analytical. The components of green space were identified and based on the review of texts, related studies and experts' opinions in the form of a researcher's questionnaire and with the approval of the relevant experts, it was designed in the form of a Likert scale (five options) and selected by 150 patients of Imam Reza Hospital and 150 patients of Bisetoon Hospital. And a total of 300 questionnaires were completed. Statistical analyzes were performed using SPSS software, and descriptive statistics (mean, standard deviation, variance) were used to describe the components of the research. In the inferential statistics section, the correlation coefficient was used to investigate the relationship between the area of ​​green space and the level of patient satisfaction with the treatment center, the independent t-test was used to compare the level of satisfaction of the patients of the two mentioned hospitals, and the Friedman test was used to identify the components of patient satisfaction. The results indicate that the feeling of satisfaction is higher in Bisetoon Medical Center compared to Imam Reza Medical Center, and among the 13 factors affecting the satisfaction of the patients of the two medical centers, the area of ​​green space has the highest visibility score and natural elements such as fountains and fountains have the lowest score. They had the privilege. In other words, with the increase in the area of ​​green space, the level of satisfaction of patients with the treatment center also increases.